RTI's Solid Sorbent-Based CO2 Capture Process: Technical and Economic Lessons Learned for Application in Coal-fired, NGCC, and Cement Plants. (July 2017) - Nelson, Thomas O.; Kataria, Atish; Mobley, Paul; Soukri, Mustapha; Tanthana, Jak
Abstract: RTI International has developed an advanced solid sorbent-based CO2 capture process for application to exhaust gas from various industrial sources – including coal-fired power plants, NGCC power plants, and cement plants. The technical and economic hurdles to solid sorbent CO2 capture are being addressed through transitioning a promising sorbent chemistry (based on supported amines) to a low-cost sorbent suitable for use in a fluidized-bed process. This sorbent has been scaled for bench- and prototype testing in both simulated coal-fired flue gas at RTI's test facility and actual cement plant flue gas at Norcem's cement plant in Brevik, Norway. Parametric testing has shown how CO2 capture performance is impacted by changing process variables. Long-term testing has generated data needed to set process conditions for operating a solids-based system for optimal performance, with continuous 90% CO2 capture, and no operational interruptions. Data collected from all phases of testing has been used to develop detailed techno-economic assessments of RTI's technology for the various CO2 emission sources applications. These detailed analyses show that RTI's technology has significant economic advantages over current amine scrubbing and potential to achieve the U.S. DOE's Carbon Capture Program's goal of >90% CO2 capture rate at a cost of < $40/T-CO2 captured by 2025.